Use of Baidu Index to Measure Public Attention toward Double Reduction Policy in China - Qinyi Tan, Fang He, Luyan Teng (Forest Chemicals Review)
The purpose of this study is to understand the public’s attention to the “double reduction” and analyze its trend and distribution, so as to know the public’s attention after the release of the double reduction policy. Using Baidu Index as the research tool and “double reduction” as the keyword, the attention and characteristics of Internet users for “double reduction” from July 24, 2021 to October 14, 2021 were obtained from three aspects: trend research, demand map and crowd portrait. It is found that the search trend of the word “double reduction" increased first and then decreased. The public pays the most attention to the “double reduction policy” and “what is the double reduction policy”. The groups paying attention to the “double reduction" are mainly distributed in Guangdong, Zhejiang and Jiangsu provinces, and most of them are women aged 30 39. At the same time, the search trend of the word “double reduction policy” is similar to that of "double reduction”. In conclusion, Baidu Index is a research instrument to study the trend of keyword search, gain insight into the change of Internet users’ demand and monitor the trend of media public opinion. The influencing factors of the change of the search volume of the word “double reduction” include the implementation of the “double reduction” policy issued by the Ministry of Education, the rectification of educational and training institutions, etc. The public is more inclined to understand the “double reduction policy” and “what is the double reduction policy” related to double reduction.